Katecheza wprowadzająca dziecko w sakramenty pokuty i Eucharystii w świetle posoborowych dokumentów Kościoła - Dziekoński, Stanisław (Studia Pastoralne, 2007)
The reflection taken up in this article shows that the documents of the Church which have been published after the II Vatican Council are a rich source of information concerning the preparation of children to the Sacrament of Penance and Reconciliation and to the Sacrament of the Eucharist. In Church teaching after the Council we find not only indicated the content, which should be present in the preparation of children to Penance and the Eucharist, but also its forms and method. The documents of the Church generally outline a certain program or direction of sacramental formation, so the demands given need to be supplemented by a catechetical and pastoral reflection, which would lead to more detailed and practical suggeststions, possible to use in pastoral and catechetical ministry. Although each elaboration must take into consideration elements that are characteristic for the introduction formation of the child to the reality of Penance and the Eucharist, which – in accordance with requirements given in the Church documents after the Council – regard above all the following issues: the preparation of children to the Sacraments of Penance and of the Eucharist takes place through a number of stages, which can be called: far, close and direct; the formation of penance and eucharistic attitudes begins already in the first months and years of the children’s lives, thus the important role of parents and family; in the process of introducing children to the reality of Penance and the Eucharist initiation catechesis has a principal role; on each of the stages of preparation one has to take into consideration the situation of the catechized, the level of personal development and family environment.